2017
DOI: 10.1016/j.ophtha.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiology of Dry Eye Disease

Abstract: Clinical and laboratory studies performed over the past few decades have discovered that dry eye is a chronic inflammatory disease that can be initiated by numerous extrinsic or intrinsic factors that promote an unstable and hyperosmolar tear film. These changes in tear composition, in some cases combined with systemic factors, lead to an inflammatory cycle that causes ocular surface epithelial disease and neural stimulation. Acute desiccation activates stress signaling pathways in the ocular surface epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
203
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 353 publications
(208 citation statements)
references
References 165 publications
(130 reference statements)
3
203
0
2
Order By: Relevance
“…This is paradoxical since if IOP increases with worsening of DED in the cold and dry weather of winter, IOP in short BUT should be higher than in normal BUT for all seasons. A possible explanation for this seeming anomaly is cornel thinning and drug penetration facilitated by disruption of the ocular surface barrier effects in DED, as previous investigations have suggested that IOP estimated as a lower value in thin cornea and intraocular drug effects of instilled eye drops depends on the drug penetration [12,41,42]. Sleep disorder, depression, and possible decreases in melatonin secretion could also contribute to the dysregulation of IOP [21,[23][24][25] in winter when sunshine decreases and DED patients suffer more stress and worsened symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This is paradoxical since if IOP increases with worsening of DED in the cold and dry weather of winter, IOP in short BUT should be higher than in normal BUT for all seasons. A possible explanation for this seeming anomaly is cornel thinning and drug penetration facilitated by disruption of the ocular surface barrier effects in DED, as previous investigations have suggested that IOP estimated as a lower value in thin cornea and intraocular drug effects of instilled eye drops depends on the drug penetration [12,41,42]. Sleep disorder, depression, and possible decreases in melatonin secretion could also contribute to the dysregulation of IOP [21,[23][24][25] in winter when sunshine decreases and DED patients suffer more stress and worsened symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the cornea benefits from the immune privilege (few immune cells, no blood vessels) and from the inhibition of inflammatory reactions. Thus, the conjunctiva naturally participates in the inflammation process to a much greater extent than the cornea and is therefore more responsive to phototoxic stress [46][47][48]. To better understand the pathways of occurring cellular death, we calculated the ratios between YO-PRO (apoptosis) and PI (necrosis) signals at various times after the end of illumination ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in our understanding of dry eye disease have been made using both chronic and acute mouse models to study the disease and it's progression (Pflugfelder and de Paiva, 2017). Genetically engineered mice have been characterized as models for chronic forms of dry eye; these include the Aire mice (Chen et al, 2017; Yeh et al, 2009) and Langerin (CD207) deficient mice (Choi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%